The effect of endurance exercise on energy and protein balance - Rolleston, Q. K. (University of Auckland, 2009)
The energy cost of endurance exercise is significant and the ability to consume enough food to maintain energy balance is critical for success. In addition maintenance of body protein stores is also critical and there is a well known relationship between energy and protein balance. The establishment of any relationship between energy and protein balance and markers of overtraining in endurance athletes is also beneficial for endurance performance. Purpose and Aims The purpose of this thesis was to investigate the effects of endurance exercise on energy balance and protein balance. The aims were to establish accurate values for EI, EE and protein balance in two endurance sports, Road Cycling and Ironman. The rationale was to determine whether endurance athletes are able to maintain energy and protein balance over periods of increased EE and whether parameters of energy and protein balance related to markers of overtraining Methods Two research projects were conducted, the first at the Tour of Southland cycle event (5 high performance male cyclists) and the second at an Ironman training camp (7 male Ironman athletes). In both studies EE was determined by the DLW technique and EI by supervised weighed diet records. Protein balance was determined by an 18-hour primed continuous infusion of 13C-leucine at the Tour of Southland and via the traditional 24-hour nitrogen balance technique at the Ironman camp. Both techniques were performed prior to and immediately after the given event. Nude body weight, blood overtraining parameters, urine samples and a mood questionnaire were collected in the mornings for analysis of daily parameters. Results The Tour of Southland: Subjects maintained energy balance with a mean EI of 27.3±3.8 MJ/day and a mean EE of 27.4 ± 2.0 MJ/day. There was no significant change in protein breakdown or parameters of overtraining. Ironman Training Camp: Athletes maintained energy balance with a mean EI of 20.27±2.91 MJ/day and a mean EE of 20.5±3.4 MJ/day and nitrogen balance was positive. There were indications of a relationship between energy and protein balance and markers of overtraining in both studies.